Intercultural competence in the scientific community: study results - A. N. Timokhovich; A. A. Elzon (Вестник университета)
The article presents the results of the study of  intercultural competence in the scientific community. The intercultural competence is an integral element of effective intercultural interaction. The theoretical bases of the research are given. The methods of the work is presented. The methodology of the integrative questionnaire of intercultural competence is applied considering four parameters: intercultural stability, intercultural interest, absence of ethnocentrism, management of intercultural interaction. The stages and results of the empirical study are described: obtaining descriptive statistics data before and after the interaction of the respondents (that represent four key segments of the target audience of the scientific organization “All-Russian Institute for Scientific and Technical Information of the Russian Academy of Sciences” (hereinafter referred to as VINITI RAS) with the stimulus advertising and information material; results of the Shapiro-Wilk test to determine normality of the primary data distribution; results of the Bartlett’s test for homogeneity of dispersion; results of the ANOVA (analysis of variance) and Wilcoxon tests to determine the statistical significance of the changes. We have formulated the conclusions about the ambiguous impact of the information materials of the scientific organisation on the representatives of the four segments; about the absence of significant communication barriers and successful interaction of the target audience of Belarusians, Kazakhs, and Kyrgyz in the framework of scientific activities with the ARISTI RAS; about the need to adapt the information materials of the organisation to cultural characteristics and preferences of different target groups.